MUSIK TONG-TONG SANGGAR SENI TARARA, BANGKALAN, MADURA - Nanang Bayu Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
Madura has a wealth of diverse traditional arts such as kejhungan, saronen, tong-tong, and gamelan. One of the interesting arts is tong-tong music. Tong-tong music is a musical ensemble dominated by wood percussion that used to function as sahur patrol music or music played to wake people up for suhoor in Ramadan. In addition, it isused to call pigeons home to return to their cages. The purpose of this study is to describe several patterns of music playing barrels of Sanggar Seni Tarara Bangkalan. This research is a qualitative research using a realist ethnographic approach. There are several repertoire of tong-tong music described in this study, including West Klapayan, East Klapayan, Ghul-ghul, and Rujurut.